Feasibility of struvite recovery process for fertilizer industry: A study of financial and economic analysis. (20th May 2017) - Yetilmezsoy, Kaan; Ilhan, Fatih; Kocak, Emel; Akbin, Havva Melda
Abstract: Struvite precipitation is widely used as an established and promising physicochemical treatment method due to its higher effectiveness for removing and recovering excess nitrogen and phosphorus from wastewater, and production of a beneficial byproduct at the end of the process. However, the majority of the literature focus not on the economic aspects of the process, but rather on the effect of different chemical combinations and changing operating conditions. In order to fulfill this gap, this study aims at a comprehensive feasibility analysis of struvite recovery process for a full-scale fertilizer production industry with a 500 m 3 /day capacity. For quantitative assessment, the experimental conditions and chemical combinations that will allow the receiving environment discharge standard for ammonium nitrogen are optimized by taking into account a large number of economic and operating parameters. The effect of change in the struvite sale price on the profit share is examined for the optimum conditions, and the investment and operating costs are calculated by getting the latest up-to-date values from the market. It is determined that when the struvite sale price is raised to 560 €/ton, the facility will obtain a net profit of €445.62/day, and be able to pay for itself in approximately six years. The findings of this study corroborate the economic feasibility of struvite recovery process as a clean and eco-friendly technology at the plant level for a sustainable nutrient management. Clearly, it appears likely that the struvite precipitation method will become more widespread in the future as an effective and non-polluting process. Graphical abstract: Highlights: Feasibility of struvite process is proposed for a full scale fertilizer facility. 98.7% of NH4 + -N can be removed by NH4 + -N MgO + NaH2 PO4 .2H2 O combination. Expenses are turned into income when the market price of struvite exceeds €482/ton. NH4 + -N recovery cost is estimated as 4.936 €/kg NH4 + -Nremoved at optimum conditions. Facility can pay for itself in approximately six years for sales price of €560/ton.